Effect of Mobile Banking on Customer Satisfaction in Commercial Banks in Nepal - Ghimire, Binod; Dhakal, Abishek (Nepalese Journal of Management Science and Research, 2023)
Customer satisfaction is an emotion a person experiences when comparing the perceived overall performance of a product to their expectations. The main purpose of this study is to analyze the effect of convenience, cost, privacy, security and responsiveness of mobile banking in customer satisfaction in Commercial Banks in Nepal. This research adopts a quantitative design wherein primary data were collected through a survey in the form of structured questionnaire distributed among 201 respondents having access of mobile banking services offered by Commercial Banks in Nepal. Pearson Correlation Matrix suggested by Levin et al., (2014) was used for statistical analysis; the results derived from the research showed Convenience, Cost, Security, and Responsiveness are significant drivers of Customer Satisfaction of Commercial Banks in Nepal. This research will be useful to higher management of the banks in developing effective strategies for mobile banking services as well as to retain their customers. Furthermore, Nepal Rastra Bank (Central Bank of Nepal) might be enthusiastic to identify the prevailing problems and technical as well as non-technical barriers concerned with the adoption of the mobile banking on customer satisfaction which will facilitate them to take necessary steps to eradicate barriers and to implement effective policies accordingly.